Lived Experiences of the Abused Elderly - Acob, Joel Rey Ugsang (Health Notions, 2018)
The study determined individual live experience of the abused elderly in the provinces of Leyte and Biliran. The study utilized qualitative phenomenology. Interviews are made and recorded, then later transcribed verbatim. Collaizi is used as a method of analysis to obtain themes of the lived experiences of the ten abused key informants. The study shows that harmed entities are female, widow within 6o to 65 years old, earning less than 2000 pesos per month and are dependently living in a nuclear family structure for 40 years. Based on their responses to the open-ended guide questions, key informants revealed emotional mistreatment being the most common form of abuse. Physical and sexual maltreatment are also evident amidst their old age. Family members and employers are the focal identified perpetrators of the elderly. Bruises on most covered areas of their body, rope burns, torn undergarments, being touched without consent are some of the objective indicators of abuse.   Themes such as family violence and workplace mistreatment are the most common form of abuse experienced. Based on the findings, the local government and concerned stakeholders were recommended to timely review existing rules protecting vulnerable adults especially its implementation.